2011
DOI: 10.1248/bpb.34.1609
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pharmacist Management on Serum Hemoglobin Levels with Renal Anemia in Hemodialysis Outpatients

Abstract: It is hoped that the clinical activities of pharmacists will enhance the quality of drug therapy. The anemia of chronic renal failure is usually characterized as a normocytic, normochromic form occurring in end-stage renal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 13 publications
1
36
0
Order By: Relevance
“…The results of this study were in agreement with previously published studies . A historical cohort study was conducted to compare the role of pharmacist‐managed erythropoietin‐stimulating agents (ESA) clinics with usual care at an ESA clinic site and at a usual‐care site.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The results of this study were in agreement with previously published studies . A historical cohort study was conducted to compare the role of pharmacist‐managed erythropoietin‐stimulating agents (ESA) clinics with usual care at an ESA clinic site and at a usual‐care site.…”
Section: Discussionsupporting
confidence: 88%
“…The results showed significant improvement in Hgb values according to hospital guidelines. The study concluded that the introduction of pharmaceutical care services in patients undergoing haemodialysis improved healthcare outcomes …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They also found that patients of ethnic-minority background reported less out-ofoffice communication with their family doctors. A number of studies looked at provider-provider relations, most often the collaboration between pharmacists and physicians (Niquille, Lattmann, & Bugnon, 2010;Ohnishi et al, 2011). In one study that included patient outcomes, Anaya et al (2008) found that collaborative drug-therapy agreements among physicians, patients, and pharmacists in diabetes-mellitus management led to better blood glucose control.…”
Section: Introductionmentioning
confidence: 99%